2021
DOI: 10.1016/j.jcot.2020.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and reliability of surgery on the lumbar spine under general versus spinal anesthesia- an analysis of 64 cases

Abstract: Quasi-experimental design purpose: Compare intra and postoperative parameters, surgeons' satisfaction, and cost-effectiveness between general anesthesia (GA) and spinal anesthesia (SA) on patients undergoing surgery in the lumbar spine surgery. Overview of literature: Surgery on the lumbar spine is the commonest surgical procedure among all spinal surgical practices. Both the GA and SA are shown to be suitable techniques for performing the surgery safely. GA is used most frequently. But, SA became increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This also reduces the time required during anesthetic emergence following surgery, which can prolong total operating room time depending on the agents that are utilized. 12,22,24 Spinal anesthesia can also be done outside of the operating room, which can improve throughput and clinical efficiency, as anesthesia can be "induced" while staff members set up operating room equipment. Decreased total operative time is a valuable benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This also reduces the time required during anesthetic emergence following surgery, which can prolong total operating room time depending on the agents that are utilized. 12,22,24 Spinal anesthesia can also be done outside of the operating room, which can improve throughput and clinical efficiency, as anesthesia can be "induced" while staff members set up operating room equipment. Decreased total operative time is a valuable benefit.…”
Section: Discussionmentioning
confidence: 99%
“…22 All included studies evaluated a combination of postoperative complication rates, total anesthesia time, operative time, blood loss, LOS, postoperative analgesic use, and anesthesia cost. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition to assessing the impact of spinal anesthesia versus general anesthesia across all surgical techniques, we performed subgroup analyses separated by procedure. Our stratified analyses showed that total anesthesia times were significantly shorter in patients who received spinal anesthesia than in those who received general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 14 articles met the inclusion and exclusion criteria from an initial pool of 552 articles. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] All articles evaluated the total intraoperative time, anesthesia duration, postoperative complications, postoperative pain, or a combination thereof. All 14 articles were included in the quantitative analysis and compared the aforementioned outcomes in patients who received general anesthesia with those who received spinal anesthesia and underwent an awake procedure.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of SA in this patient population and the benefits of SA over GA with respect to hemodynamic stability, postoperative nausea, vomiting, pain control, and cost-effectiveness. 2-5…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of SA in this patient population and the benefits of SA over GA with respect to hemodynamic stability, postoperative nausea, vomiting, pain control, and cost-effectiveness. [2][3][4][5] The authors hypothesized that SA would be associated with decreased postoperative fatigue and cognitive dysfunction, translating to improved quality of life. The authors report decreased fatigue in the SA group at 1 month after the operation based on a fatigue visual analog scale (VAS) (scored 1-10, no fatigue to extreme fatigue) and the Chandler Fatigue Score (CFQ).…”
mentioning
confidence: 99%